TECHNOLOGIES FOR TEACHING ENGLISH PHRASEOLOGICAL UNITS (TAMADDUN NURI JURNALI, 2024)
English language learners spend a lot of time learning vocabulary. In particular, there is little information in textbooks on the study of phraseology, and students face difficulties in using learned phraseological units in real situations. The article analyzes the methods used in working with phraseological units.